MR Vaccination in Pregnancy and its Subsequent Complications - Z. Shahhosseini, M.Sc (Journal of Mazandaran University of Medical Sciences, 2007)
Background and purpose: MR vaccination is prohibited among pregnant women, therefore pregnancy is recommended three months after vaccination. On the other hand, pregnant women acquiring these diseases face unwanted complications. We tried to determine the frequency of congenital disorders in the newborns of the vaccinated pregnant women under 25 years in Mazandaran province.Materials and Methods: This historical cohort study was done by consent method on 1031 cases throughout Mazandaran province. 406 cases out of the population were vaccinated without prior information about their pregnancy. The data were collected by questionnaires through referring to their healthcare files and telephone contacts just to make sure about their vaccination conditions. The data obtained from these cases along with the data from 493 pregnant women who were not vaccinated during the years 2002-2003 were statistically analyzed.Results: Pregnancy complications were observed in 58 (6.5%) subjects; 24 (41.38%) in the control group and 34 (58.62%) in the case group. The rate of complications in the subjects under the study was as follows: premature delivery in 27 (46.57%) subjects; 8 (29.62%) in the control group and 19 (70.38%) in the case group; weight under 2500 gram at birth in 19 (32.75%) subjects; 12 (63.16%) in the control group and 7 (36.84%) in the case group; still birth in 6 (10.34%) subjects 1 (16.67%) in the control group and 5 (83.33%) in the case group; abortion in 6 subjects (10.34%); 2 (23.33%) in the control group and 4 in (66.67%) in the case group. Only one person in the control group had intra uterine growth retardation. No significant pregnancy complication difference was observed between the case and the control groups in this study (P>0.05)Conclusion: Results of this study and the related researches indicate that though MR vaccination during pregnancy is safe, the randomly performed vaccination of pregnant women, should be advised and the followed up for the probable unwanted complications.